Curits Float Plane - Washington State University Vancouver Library; http://library.vancouver.wsu.edu/ (1922)
Roy Jones at Bear Ketchikan, Alaska in a 180hp Pusher Model. The pontoon plane was built for the Navy. 3.5x5 in.